Microfinance and Diversification. (18th April 2022) - Bandiera, Oriana; Burgess, Robin; Deserranno, Erika; Morel, Ricardo; Rasul, Imran; Sulaiman, Munshi; Thiemel, Jack
Abstract : The bulk of the world's extreme poor work in subsistence agriculture. Diversification out of this activity is often seen as the sine qua non of economic development. We evaluate whether the roll‐out of a mainstay development intervention—microfinance—into poor, agricultural and largely unbanked populations in rural Uganda helps borrowers to diversify into non‐agricultural labour activities. The new microfinance product is targeted to women, and differs from existing sources of formal and informal credit in that it allows them to borrow larger amounts but has inflexible repayment dates and the use of funds is monitored. We find that the arrival of microfinance enables women to diversify out of agriculture and into service‐based activities such as small‐scale trading. This low‐level structural change, however, is not transformative in that it does not lead—at least after two years—to significant uplifts in earnings, consumption, savings, investment and overall wealth.